2010
DOI: 10.1111/j.1349-7006.2010.01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of estrogen‐producing and metabolizing enzymes in benign breast disease: Comparison with normal breast and breast carcinoma

Abstract: It is well known that estrogens play important roles in the cell proliferation of breast carcinoma. Benign breast disease (BBD) contains a wide spectrum of diseases, and some are considered an important risk factor for subsequent breast carcinoma development. However, the significance of estrogens in BBD has remained largely unknown. Therefore, in this study, we examined tissue concentrations of estrogens and immunolocalization of estrogenproducing ⁄ metabolizing enzymes in BBD, and compared these findings wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
(68 reference statements)
2
16
0
2
Order By: Relevance
“…Here, we showed that the immunoreactivity profile of these enzymes in the macaque breast is comparable to that in the normal human breast (50), supporting the translational potential of the macaque breast model for studying agents that may alter estrogen metabolism. No effects of soy IF exposure on steroidogenic enzyme expression in the pubertal breast were observed.…”
Section: Discussionsupporting
confidence: 63%
“…Here, we showed that the immunoreactivity profile of these enzymes in the macaque breast is comparable to that in the normal human breast (50), supporting the translational potential of the macaque breast model for studying agents that may alter estrogen metabolism. No effects of soy IF exposure on steroidogenic enzyme expression in the pubertal breast were observed.…”
Section: Discussionsupporting
confidence: 63%
“…The extraction methods and derivatization procedures for tissue steroid assays often use the prostate, skin and breast [24,[53][54][55], as well as the adrenal gland, testis, liver, ovary and uterus, as examples [56,57]. With the availability of more sensitive mass spectrometers and ultra-performant liquid chromatography (UPLC), LC-MS/MS has become an efficient technique for the measurement of steroids with low limits of quantitation (LLOQ) with values down to the 5 pg/mL level for Testo and 40 pg/mL for 4-dione without derivatization [58].…”
Section: Discussionmentioning
confidence: 99%
“…Since breast adipose tissue is the major site of estrogen biosynthesis, its local delivering is likely involved in cancer progression. As matter of fact, estrogen level in breast tissues results 10 times greater than in blood as a consequence of high aromatase activity and tumor cells release stimulatory factors that amplify aromatase expression (Sasaki et al 2010). Breast tumor cells also influence and modify the surrounding tissue microenvironment.…”
Section: Cross-talk Between Mature Adipocytes and Breast Cancer Cellsmentioning
confidence: 99%